Radiación ultravioleta, epidemiología del cáncer cutáneo y factores de riesgo - Zemelman D., Viviana (Revista Hospital Clínico Universidad de Chile, 2007)
Skin cancer has increased in the last decades throughout the world. This may be explained by an increase exposure of individuals to UV radiation, mainly due to the hole in the ozone layer and also due to an increase in leisure time an the desire to possess a suntan. In this article, skin cancer epidemiology in Chile and skin cancer epidemiology throughout the world are reviewed; also, skincancer risk factors such as skin phenotype and sun exposure behaviour in the Chilean population are discussed. Anatomical localization of Malignant Melanoma (MM) is an important issue related to the prognosis of the tumour. In this article, MM anatomical location in the Chilean population is also reviewed and compared with the MM´s localization in other population. This article summarized results on the skin cancer epidemiology and risk factors on the Chilean population.